2016
DOI: 10.1186/s41038-016-0029-9
|View full text |Cite
|
Sign up to set email alerts
|

New perspectives of volemic resuscitation in polytrauma patients: a review

Abstract: Nowadays, fluid resuscitation of multiple trauma patients is still a challenging therapy. Existing therapies for volume replacement in severe haemorrhagic shock can lead to adverse reactions that may be fatal for the patient. Patients presenting with multiple trauma often develop hemorrhagic shock, which triggers a series of metabolic, physiological and cellular dysfunction. These disorders combined, lead to complications that significantly decrease survival rate in this subset of patients. Volume and electrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…They have also shown the lack of cognitive imbalance later on, but with no significant differences at 7 days (p = 0.062), and at 90 days (p = 0.372) [46]. Postoperative complication rate has been shown to vary between 20% and 42% [47]; they have an impact both on the clinical outcome of patients, as well as on the OR management and patient outflow [48]. This is due to longer times of stay in the recovery room and longer hospital length of stay [49][50][51][52].…”
Section: Discussionmentioning
confidence: 98%
“…They have also shown the lack of cognitive imbalance later on, but with no significant differences at 7 days (p = 0.062), and at 90 days (p = 0.372) [46]. Postoperative complication rate has been shown to vary between 20% and 42% [47]; they have an impact both on the clinical outcome of patients, as well as on the OR management and patient outflow [48]. This is due to longer times of stay in the recovery room and longer hospital length of stay [49][50][51][52].…”
Section: Discussionmentioning
confidence: 98%
“…They also showed the lack of cognitive imbalance later on, but with no significant differences at 7 days (p = 0.062) and at 90 days (p = 0.372) [ 46 ]. Post-operative complication rate has been shown to vary between 20% and 42% [ 47 ]; they have an impact both on the clinical outcome of patients as well as on the OR management and patient outflow [ 48 ]. This is due to longer times of stay in the recovery room and a longer hospital length of stay [ 49 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that hypercholesterolemia can be an important index for negative prognosis in these patients, especially because of the complex interactions that cholesterol has with protein fragments in plasma. Moreover, it has been noticed that hypercholesterolemia interfaces with the augmentation of the systemic inflammatory response [69]. Chiarla et al conducted a study in order to identify correlations between plasmatic cholesterol levels and a series of metabolic changes in septic patients.…”
Section: Molecular and Pathophysiological Aspects Of Metabolismmentioning
confidence: 99%